IMMUNOGLOBULIN/HISTAMINE COMPLEX IN ALLERGIC DISEASES: A SYSTEMATIC REVIEW - K, Sivanandhan; Godse, Kiran; Pereira, Carlton; Patodiya, Shalini; Modi, Gautam; Banerjee, Saswata; Patel, Hemal (International Journal of Pharma and Bio Sciences, 2026)
Histaglobulin or immunoglobulin/histamine complex (IHC) has been used globally to treat allergic diseases for several decades. It is a sterile, non-allergen-specific immunotherapeutic agent made up of histamine dihydrochloride and human immunoglobulin as the main components. Histaglobulin effectively treats allergic rhinitis, bronchial asthma, chronic urticaria, atopic dermatitis, and many other allergic conditions. It can be given over a long period without any safety concerns. However, despite being used for several decades for chronic allergic conditions, no reviews or systematic reviews (SRs) comprehensively cover the efficacy and safety of histaglobulin/IHC in various chronic allergic conditions. The publicly available literature on its efficacy and safety in various chronic allergic conditions consists only of small open-label prospective studies, case reports, or case series. This systematic review was undertaken to provide a comprehensive view of the efficacy, safety, and dosing schedule of histaglobulin in common chronic allergic dermatological and respiratory conditions such as chronic urticaria, atopic dermatitis, allergic rhinitis, and bronchial asthma. Further, the SR explored the role of histaglobulin in other conditions such as psoriasis, cutaneous drug allergies, Pfeiffer-Weber-Christian disease with multiple food allergies/atopic dermatitis, and primary eosinophilic colitis. The SR also covers the role of histaglobulin in treating allergic psychiatric manifestations. This is the first SR that documented and concluded that histaglobulin could safely achieve a long-term symptoms-free state in chronic allergic conditions such as chronic urticaria, atopic dermatitis, allergic rhinitis, and asthma. The studies captured in the SR show that histaglobulin can be given for prolonged periods as weekly injections or more frequently (at intervals of 4 days) until completely symptom-free or with significant improvement from allergic symptoms. The SR also identified the need for large multicentre prospective, double-blind, randomized controlled trials, prospective well-designed open-label trials, and observational real-world studies to document the efficacy (including remission) and safety benefits of histaglobulin in various types of chronic allergic conditions not responding to conventional treatments.